2021
DOI: 10.1002/bco2.65
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the association between socioeconomic status and bladder cancer survival with hospital type, comorbidities, and treatment delay as mediators

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 72 publications
0
2
0
2
Order By: Relevance
“…У хворих на РСМ була показана залежність між соціально-економічним статусом, що виражалось у зменшенні п'ятирічної КСВ, загальної виживаності) та збільшенням ризику канцер-специфічної смертності [95,96]. Аналіз даних GLOBOCAN продемонстрував позитивну кореляцію між валовим внутрішнім продуктом на душу населення та РСМ у чоловіків (r=0,48) та жінок (r=0,44).…”
Section: Cоціально-економічне положенняunclassified
See 1 more Smart Citation
“…У хворих на РСМ була показана залежність між соціально-економічним статусом, що виражалось у зменшенні п'ятирічної КСВ, загальної виживаності) та збільшенням ризику канцер-специфічної смертності [95,96]. Аналіз даних GLOBOCAN продемонстрував позитивну кореляцію між валовим внутрішнім продуктом на душу населення та РСМ у чоловіків (r=0,48) та жінок (r=0,44).…”
Section: Cоціально-економічне положенняunclassified
“…Однак наведена залежність не була статистично значущою в мультиваріантному лінійному регресивному аналізі, скоригованому для курців тютюну [97]. Можливими медіаторами впливу соціально-економічного статусу на перебіг РСМ та результати радикальної цистектомії вважаються тип лікарні, де проходить лікування хворий на РСМ, коморбідний стан хворого, а також відтермінування лікування [96].…”
Section: Cоціально-економічне положенняunclassified
“…SES may influence various aspects of compliance with care, especially given the multi-modal and multi-disciplinary delivery of treatment regimens in MIBC. These include, but are not limited to, shared decision-making, treatment delays, hospital type/resources, insurance accessibility, and financial toxicity [8]. Even after adjusting for such aforementioned social determinants and clinical variables, Washington et al showed that higher income was associated with an increased likelihood of receiving guideline-based, appropriate MIBC treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although this is not a traditional review, this type of paper effectively highlights the dilemmas in this space and where future research needs to focus. The review by Russel et al 2 is a traditional systematic review in bladder cancer. They focused on socioeconomic status as a predictor of survival but could also show relationships with modifiable risk factors such as treatment delays.…”
mentioning
confidence: 99%